Steering lock and brake / Muhammad Hakimi Mohd Basir ... [et al.] - Mohd Basir, Muhammad Hakimi; Wan Kefli, Wan Aiman Aqil; Mohd Safawi, Ahmad Safwan; Mohammad Zaini, Mohammad Firdaus
The steering lock & brake was made to help people secured their car from theft. The aim of this steering lock is used to protect the steering and brake pad and will protect the car from theft. The function is like a normal steering lock but our product is the best because our products have good material and mechanism. Besides, this steering lock can increase the safety of the consumer while they left their car behind. Especially for the customer that need more protection for their car